THE USE OF COOPERATIVE MODEL TYPE SCRIPT WITH IMAGE MEDIA IN IMPROVING SOCIAL SCIENCE LEARNING FOR THE FOURTH GRADE STUDENTS OF SD NEGERI SUMINGKIR 01 IN ACADEMIC YEAR 2014/2015 - Rohmah, Tri Nur (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: THE USE OF COOPERATIVE MODEL TYPE SCRIPT WITH IMAGE MEDIA IN IMPROVING SOCIAL SCIENCE LEARNING FOR THE FOURTH GRADE STUDENTS OF SD NEGERI SUMINGKIR 01 IN ACADEMIC YEAR 2014/2015. The objectives of this research iis to improve students? learning outcomes of social science learning by using Cooperative model type Script with image media. This research was conducted in three cycles. Each cycle consisted of the planning, implementation, observation, and reflection. The results of this research is the increase process and student learning outcomes. The subjects were fourth grade students of SD Negeri Sumingkir 01. Data was collected using tests and non-test techniques. The validity of the data was analyzed using triangulation of sources and triangulation of techniques. Conclusion of research is the use of Cooperative model type Script can improve students? learning outcomes of social science.  Keywords: Cooperative Script, social science learning, image media.